2021
DOI: 10.3389/fcell.2021.787485
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor-Stromal Interactions in Pancreatic Cancer: Impact of Collagens and Mechanical Traits

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has one of the worst outcomes among cancers with a 5-years survival rate of below 10%. This is a result of late diagnosis and the lack of effective treatments. The tumor is characterized by a highly fibrotic stroma containing distinct cellular components, embedded within an extracellular matrix (ECM). This ECM-abundant tumor microenvironment (TME) in PDAC plays a pivotal role in tumor progression and resistance to treatment. Cancer-associated fibroblasts (CAFs), being a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 237 publications
(331 reference statements)
0
29
0
Order By: Relevance
“…Tumor ECM not only serves as a simple structural support but also plays a pivotal role in modifying tumor cell behavior. For example, aberrant ECM accumulation attributes to increased interstitial pressure and the collapse of capillary vessels, leading to the decreased delivery of blood flow and therapeutic agents, which results in a hypoxic microenvironment and altered drug response [47][48][49]. Signaling pathways, such as the integrin signaling pathway, also contribute to the regulation of cellular machinery in pancreatic cancer cells [50].…”
Section: Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor ECM not only serves as a simple structural support but also plays a pivotal role in modifying tumor cell behavior. For example, aberrant ECM accumulation attributes to increased interstitial pressure and the collapse of capillary vessels, leading to the decreased delivery of blood flow and therapeutic agents, which results in a hypoxic microenvironment and altered drug response [47][48][49]. Signaling pathways, such as the integrin signaling pathway, also contribute to the regulation of cellular machinery in pancreatic cancer cells [50].…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Among the stromal cell-derived ECM molecules, collagens are the predominant components, accounting for more than 90% of ECM proteins in pancreatic cancer stroma and chronic pancreatitis [45]. Collagens include 29 known superfamily members in vertebrates [49]. Proteomic analyses have revealed that approximately 90% of the total collagens in PDAC tissues are type I and type III fibrillar-type collagens [45], which are predominantly produced by stromal cells, especially ACTA2, the HUGO (Human Genome Organization)approved official symbol for actin alpha 2, smooth muscle; HGNC ID: 130; it is also known as alpha smooth muscle actin or αSMA-expressing fibroblasts [53].…”
Section: Collagensmentioning
confidence: 99%
“…Increased tissue stiffness, typically a result of ECM remodeling, is seen in many pathological microenvironments, such as breast and pancreatic tumors, lung and liver fibrosis, and cardiovascular disease [26,[69][70][71][72][73][74][75][76][77][78] and has even been considered as a prognostic factor in cancer progression [79,80]. Our data indicate that ATF3 is an early and major transcriptional target of increased ECM stiffness.…”
Section: Discussionmentioning
confidence: 73%
“…We have focused this study on the effect of CAP in PSCs because the stroma regulates the molecular interactions with the ECM, is responsible for the remodelling of the TME in PDAC, and facilitates the invasion and metastasis of cancer cells [46]. The matrix metalloproteinases (MMPs), mostly secreted by PSCs, but also by PDAC cells, participate actively in this process [47].…”
Section: Discussionmentioning
confidence: 99%